2019
DOI: 10.21203/rs.2.9614/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual-biased gene expression of olfactory-related genes in the antennae of Conogethes pinicolalis (Lepidoptera: Crambidae)

Abstract: Background Conogethes pinicolalis (Lepidoptera: Crambidae), is similar to Conogethes punctiferalis (yellow peach moth) and its host plant is gymnosperms, especially for masson pine. So far, less literature was reported on this pest. In present study, we sequenced and characterized the antennal transcriptomes of male and female C. pinicolalis for the first time. Results Totally, 26 odorant-binding proteins (OBP) genes, 19 chemosensory proteins (CSP) genes, 55 odorant receptors (OR) genes and 20 ionotropic recep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…It has been accepted that OBPs, including OBPs, GOBPs and PBPs, exhibit different functions in odorant recognition. Multiple research studies have demonstrated that both OBPs and GOBPs play an essential role in the recognition of host plant volatiles, and PBPs exhibits strong interaction with sex pheromones in lepidopteran insect species, including C. punctiferalis (Brito et al., 2016; Jing, Zhang, Bai, et al., 2020; Zhang et al, 2017). However, recent studies suggest that general OBPs (OBPs and GOBPs) also interact with sex pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…It has been accepted that OBPs, including OBPs, GOBPs and PBPs, exhibit different functions in odorant recognition. Multiple research studies have demonstrated that both OBPs and GOBPs play an essential role in the recognition of host plant volatiles, and PBPs exhibits strong interaction with sex pheromones in lepidopteran insect species, including C. punctiferalis (Brito et al., 2016; Jing, Zhang, Bai, et al., 2020; Zhang et al, 2017). However, recent studies suggest that general OBPs (OBPs and GOBPs) also interact with sex pheromones.…”
Section: Discussionmentioning
confidence: 99%